2021
DOI: 10.3389/fped.2021.690863
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of C-Reactive Protein for Early Postoperative Complications in Children After Hypospadias Surgery

Abstract: Background: This study explored the predictive value of postoperative C-reactive protein in children with hypospadias for postoperative complications and the risk factors.Methods: The clinical and follow-up data of 106 children with hypospadias who were treated with operations at Kunming Children's Hospital in 2020 were, respectively, analyzed. According to the occurrence of postoperative complications, the patients were divided into two groups: 25 patients with postoperative complications were the complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Our study found that LUD was an independent risk factor for hypospadias postoperative complications, which is consistent with previous studies 2,16–20 . Longer urethral defects require a greater amount of urethral repair material and a larger aspect ratio of the flap used in the urethral reconstruction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that LUD was an independent risk factor for hypospadias postoperative complications, which is consistent with previous studies 2,16–20 . Longer urethral defects require a greater amount of urethral repair material and a larger aspect ratio of the flap used in the urethral reconstruction.…”
Section: Discussionsupporting
confidence: 92%
“…15 Our study found that LUD was an independent risk factor for hypospadias postoperative complications, which is consistent with previous studies. 2,[16][17][18][19][20] Longer urethral defects require a greater amount of urethral repair material and a larger aspect ratio of the flap used in the urethral reconstruction. Consequently, ensuring sufficient blood supply for longer urethral defects becomes challenging, which hinders flap growth and anastomotic healing.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative C-Reactive Protein value (24 h after surgery) is a reliable marker for a possible complication after hypospadias surgery (94).…”
Section: Others Samir Et Al 2021mentioning
confidence: 99%